Understanding Covid-19 - Hustad, Douglas (Core library guide to Covid-19, 2021)
COVID-19 is a disease caused by a virus called SARS-CoV2. Like all viruses, it is far too small to be seen by the naked eye. Yet this virus and the disease it caused had an enormous impact on the world. Understanding COVID-19 explores how the virus and the disease work, examining what made them so dangerous and what health officials learned about fighting them.